Structural parameter optimization of a furrow opener based on EDEM software - Wang, Longjie; Zhou, Bin; Wan, Chang; Zhou, Ling (International Journal of Agricultural and Biological Engineering, 2024)
To reduce the ditching resistance of a furrow opener during operation, single-factor and multiple-factor combinations were used to explore the influence of the furrow opener’s advance speed, blade opening angle, and width on the ditching resistance based on the discrete element method (DEM). A DEM simulation of the furrow opener was developed. Upon changing these influencing factors, the parameters with the least resistance to operation were identified. Furrow openers were fabricated according to the optimized results, and soil trench tests were carried out. Simulations and soil groove tests showed that the minimum ditching resistance was 58.54 N when the current advance speed was 4.47 m/s, the blade opening angle was 32.02°, and the furrow opener width was 51.45 mm. The error between the simulated value of the ditching resistance and the soil trench test was within 10%, and the trends of resistance change were essentially the same, indicating that it is feasible to optimize the structural parameters of a trench furrow opener using DEM. These research results can provide a reference for the parameter optimization of furrow openers. Keywords: furrow opener, discrete element, optimization, ditching resistance DOI: 10.25165/j.ijabe.20241703.7927 Citation: Wang L J, Zhou B, Wan C, Zhou L. Structural parameter optimization of a furrow opener based on EDEM software. Int J Agric & Biol Eng, 2024; 17(3): 115-120.